Progress in research on predictors of adverse outcomes in patients with nasal inflammatory diseases - Liao, Jiang-Xue; Lin, Xin; He, Jing; Feng, Hua-Jun; Liang, Zhuo-Ping; Qin, Gang (Frontiers in Immunology, 2026)
Nasal inflammatory disease has a complex pathogenesis, high incidence and long disease course. Complete resolution is often challenging, and these diseases are closely related to upper and lower respiratory tract diseases. For common nasal inflammatory diseases, such as chronic rhinosinusitis (CRS), allergic rhinitis (AR), and fungal rhinosinusitis (FRS), adverse outcomes, such as repeated inflammation, AR combined with asthma, and postoperative recurrence, often occur despite standardized treatments, causing great distress to patients and increasing societal costs due to the need for long-term and repeated treatments. Therefore, the identification of early predictors of unfavorable outcomes of nasal inflammatory diseases is important for achieving early diagnosis, intervention and treatment of nasal inflammatory diseases. This paper summarizes the progress in research on the role of indicators, such as inflammatory cytokines, inflammatory cells, metabolites, nasal flora, and clinical parameters, in predicting poor outcomes in patients with nasal inflammatory diseases.